2012
DOI: 10.1128/aem.01081-12
|View full text |Cite
|
Sign up to set email alerts
|

Internalization and Dissemination of Human Norovirus and Animal Caliciviruses in Hydroponically Grown Romaine Lettuce

Abstract: ABSTRACTFresh produce is a major vehicle for the transmission of human norovirus (NoV) because it is easily contaminated during both pre- and postharvest stages. However, the ecology of human NoV in fresh produce is poorly understood. In this study, we determined whether human NoV and its surrogates can be internalized via roots and disseminated to edible portions of the plant. The roots of romaine lettuce growing in hydroponic feed water were inoculated with 1 × 106<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 54 publications
2
82
1
Order By: Relevance
“…However, other studies have used various concentrations of FBS for propagation of these viruses. For example, MNV was propagated in 2% (7,33) or 5% FBS (34), TV in 2% (9, 33) or 10% (13,35), and FCV in 0 to 2% (19,36,37) or 10% FBS (7,21,38). Serum contains lipids, attachment factors, and stabilizing and detoxifying factors needed to inhibit proteases (39).…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have used various concentrations of FBS for propagation of these viruses. For example, MNV was propagated in 2% (7,33) or 5% FBS (34), TV in 2% (9, 33) or 10% (13,35), and FCV in 0 to 2% (19,36,37) or 10% FBS (7,21,38). Serum contains lipids, attachment factors, and stabilizing and detoxifying factors needed to inhibit proteases (39).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the speed with which it acts, this technology offers several advantages over continuous UV treatment. It could be used to deal with contamination issues, including contamination of shellfish by municipal sewage released into marine product growing areas (47) and contamination of vegetables by irrigation (48,49).…”
Section: CMmentioning
confidence: 99%
“…A number of studies reported that HuNoV and its surrogates can internalize inside lettuce and spinach plants under normal conditions (28,43,44) and in lettuce under certain biotic and extreme abiotic stress a Numbers in bold indicate a significant effect (P Ͻ 0.05) for that factor. Statistical analyses were performed by two-way ANOVA.…”
Section: Discussionmentioning
confidence: 99%